Determining elements in cases of failure and dissolution of cooperatives: a systematic review (Gestão & Regionalidade, 2024)
This work intends to contribute to the literature on cooperative societies, in particular, on which elements have been decisive in cases of discontinuity of these organizations. A qualitative approach of an exploratory nature was used as a methodological resource, through a systematic literature review. The bibliography retrieved from the databases of Scopus and the Portal of Periodicals of the Coordination for the Improvement of Higher Education Personnel (Capes), in the period from 1971 to 2021, resulted in 54 and 97 works respectively, which were later analyzed and categorized. The results show that the main contributing factors to the failure and dissolution of cooperatives have been identified and associated with external factors, observable in: (i) cooperatives acting as a development mechanism, (ii) cooperatives as operators of public policies; and internal factors: (iii) characteristics inherent in the cooperative organization, (iv) government interventions in the environment of cooperative action, and (v) political, economic and legal issues.
Keywords: failure of cooperatives; dissolution of cooperatives; cooperatives.